(untitled) (Journal of Hama University, 2024)
This study was conducted on 450 hybrid (Habbard Flex) chicks, in Latakia Governorate, during the period of 2022. Day-old chicks were randomly distributed into six different treatments, each treatment had three replicates according to the color of the bulbs (green G24Lux, blue B24Lux, green-blue alternation G-B 24Lux , a mixture of green and blue Mix B+G 28Lux , white W65Lux, yellow Y80Lux). The study aimed to evaluate the effect of using different colors of lighting on some behavioral and hematological indicators of broiler and to determine the most appropriate lighting color that enhances the health, calm and well-being of the birds. The results showed a significant increase (p≤0.01) in the number of red cells in the blood of birds, and the highest value was to the TMix G+B treatment (2.96) and the lowest to the TW treatment (2.58) million cell/mm3 respectively. While for the number of white cells the highest value was to the TY (26.75) and the lowest to T G-B (24.11) thousand cells/mm3 respectively. The values for glucose concentration in blood serum were TW (193.71) and TY (197.18) mg/100 ml respectively. And the highest value of hemoglobin concentrations was recorded to TMix G+B(11.86) g/dl. In addition from the results a significant decrease (p≤0.01) was record to the percentage of albumin in birds exposed to TY (16.28) g/dl, as well as a decrease in the total protein value of birds exposed to traditional lighting, the lowest value was at the TW (30.05) g/dl. An increase in the hematocrit value at T G-B (31.76) %. While the highest value for cholesterol was at TY (163.46) mg/dl, also the results showed increase in the value of the liver enzymes ALT and AST for the birds exposed to incandescent lighting, it reached at the TY to (38.74) and (39.34) U/L respectively. The results of viewing and monitoring the behavior of birds indicated that the birds of the two treatments (TMix G+B) and (TG-B) were outperformed to the rest of the other treatments in terms of natural movement, activity, vitality, and the ability to see the manholes and feeders. It is concluded that the treatments (TMIX G+B or T G-B(, improves its behavioral and blood indicators and reduces the level of stress, which may be reflected in its health condition and productive performance.